Genotyping and investigating capsular polysaccharide synthesis gene loci of non-serotypeable Streptococcus suis isolated from diseased pigs in Canada. (January 2018) - Zheng, Han; Qiu, Xiaotong; Roy, David; Segura, Mariela; Du, Pengchen; Xu, Jianguo; Gottschalk, Marcelo
Abstract Streptococcus suis (S. suis ) is an important swine pathogen and an emerging zoonotic agent. Most clinicalS. suis strains express capsular polysaccharides (CPS), which can be typed by antisera using the coagglutination test. In this study, 79S. suis strains recovered from diseased pigs in Canada and which could not be typed using antisera were further characterized by capsular gene typing and sequencing. Four patterns ofcps locus were observed: (1) fifteen strains were grouped into previously reported serotypes but presented several mutations in theircps loci, when compared to available data from reference strains; (2) seven strains presented a complete deletion of thecps locus, which would result in an inability to synthesize capsule; (3) forty-seven strains were classified in recently described novelcps loci (NCLs); and (4) ten strains carried novel NCLs not previously described. Different virulence gene profiles (based on the presence ofmrp, epf, and/orsly ) were observed in these non-serotypeable strains. This study provides further insight in understanding the genetic characteristics ofcps loci in non-serotypeableS. suis strains recovered from diseased animals. When using a combination of the previously described 35 serotypes and the complete NCL system, the number of untypeable strains recovered from diseased animals in Canada would be significantly reduced.